All-printed capacitors from graphene-BN-graphene nanosheet heterostructures - COLEMAN, JONATHAN; HALLAM, TOBY; FINN, DAVID JOSEPH (My University, 2016)
This work aims to develop methodologies to print pinhole-free, vertically stacked heterostructures by sequential deposition of conductive graphene and dielectric h-BN nanosheet networks. We achieve this using a combination of inkjet printing and spray-coating to fabricate dielectric capacitors in a stacked graphene/BN/graphene arrangement. Impedance spectroscopy shows such heterostructures to act as series combinations of a capacitor and a resistor, with the expected dimensional dependence of the capacitance. The areal capacitance ranges from 0.24 to 1.1 nF/cm2 with an average series resistance of ∼120 kΩ. The sprayed BN dielectrics are pinhole-free for thicknesses above 1.65 μm. This development paves the way toward fabrication of all-printed, vertically integrated, multilayer devices.
Keywords: conductive graphene and dielectric h-BN nanosheet networks; conductive graphene and dielectric h-BN nanosheet networks